PEMANFAATAN KECERDASAN BUATAN DALAM PERSONALISASI PEMBELAJARAN MAHASISWA - Falah, Miftahul; Florensia, Yesinta (Jusikom : Jurnal Sistem Komputer Musirawas, 2025)
The development of Artificial Intelligence technology has presented new opportunities in improving the quality of education, especially in creating adaptive and personalized learning systems. In higher education, the main challenge in the learning process is the differences in student characteristics such as learning styles, initial level of understanding, and learning motivation. This inequality often makes it difficult for lecturers to deliver material evenly and effectively. This study aims to examine the extent to which the use of AI technology can improve the personalization of student learning and its impact on learning outcomes. The research method used was a quasi-experiment with a pre-test and post-test approach to 62 students involved in AI-based learning systems. The instruments used included learning outcome tests and student perception questionnaires. The results of the study showed a significant increase in learning outcomes after the implementation of AI, with an average post-test score higher than the pre-test. These findings indicate that the application of AI in learning not only improves academic outcomes but also creates a more personalized and adaptive learning experience. The conclusion of this study emphasizes the importance of integrating AI into modern learning systems in order to address the challenges of differentiating student characteristics more effectively.